Length-weight relationship and growth parameters of the commercial fish Pagellus erythrinus (Linnaeus, 1758) (Actinopterygii: Sparidae) from northern and southern Tunisia - Fassatoui, Chiheb; Hmida, Leila; Jenhani, Amel Ben Rejeb; Romdhane, Mohamed Salah (Biological Letters, 2019)
Based on length, weight, and age data, we examined allometry and growth parameters for common pandora, Pagellus erythrinus, commercially collected seasonally from northern and southern Tunisian coasts in 2007. A total of 370 specimens (14–27.5 cm in length) were used to assess the allometric variation at seasonal scales. The slope b values (regression coefficient) of the length-weight relationship varied between 2.494 to 3.237, indicating (roughly) an isometric to negative allometric growth pattern. The allometric relationship, as a proxy for fish condition, seems to be affected by seasons and sex in the northern population, while only seasons seem to have a strong effect in the southern population, as indicated by ANOVA. The von Bertalanffy growth parameters were identified at L ∞ = 34.076 and 28.017 cm, k = 0.153 and 0.150/year, and t0 = −1.922 and −3.961 years for the northern and southern sample, respectively.